Identification of Factors Affecting Consumers In Buying Local Chocolate Products - Bachtiar, Wildan Fajar; Anoraga, Satria Bhirawa; Purwaditya, Anjar Kistia (Journal of Agri-Food Science and Technology, 2020)
Yogyakarta has become a potential market for culinary industries. One of the emerging products, which becomes a typical souvenir from Yogyakarta, is local chocolate products. Some of the local chocolate producers continue to grow through their uniqueness and different sales points. The objective of this study is to investigate factors affecting of consumer decision making in purchasing local chocolate as a souvenir. This study was conducted in September 2019 through primary data collection in Yogyakarta. This research study involves exploration of significant target consumers. The total sample of 31 respondents were collected by accidental sampling. The results indicate that consumers highlighted promotion as the most important marketing factor that influences the purchasing decision for local chocolate products. On the other hand, consumers show that the products' quality and store are more important than the prices. Premium quality products, attractive and economical packaging, and giving product samples, ranked as the top three influential promotion sub-factors related to local chocolate product selection. Consumers who have higher educational backgrounds will focus on quality. The price factor becomes the last consideration, which is the variable price versus the number of contents in one package.